Penerapan Empty Chair Therapy pada Individu Dewasa dengan Diagnosa Episode Depresif Ringan - Erika Prima Yola; Pranungsari, Dessy (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Depression has a serious impact that includes emotional, motivational, behavioral, physical and cognitive domains. One of the vulnerability factors for depression is the presence of stressful life events. According to the Humanistic view, a person can experience depression when they cannot fill their existence with meaning. Gestalt counseling is a counseling method that is often used in the humanistic approach because it has the main goal of achieving awareness centered on